Autonomous Taxi Service Design and User Experience. Issue 5 (15th March 2020) - Kim, Sangwon; Chang, Jennifer Jah Eun; Park, Hyun Ho; Song, Seon Uk; Cha, Chang Bae; Kim, Ji Won; Kang, Namwoo
ABSTRACT: As autonomous-vehicle technologies advance, conventional taxi and car-sharing services are being combined into a shared autonomous vehicle service, and through this, it is expected that the transition to a new paradigm of shared mobility will begin. However, before the full development of technology, it is necessary to accurately identify the needs of the service's users and prepare customer-oriented design guidelines accordingly. This study is concerned with the following problems: (1) How should an autonomous taxi service be designed and field-tested if the self-driving technology is imperfect? (2) How can imperfect self-driving technology be supplemented by using service flexibility? This study implements an autonomous taxi service prototype through a Wizard of Oz method. Moreover, by conducting field tests with scenarios involving an actual taxi, this study examines customer pain points, and provides a user-experience-based design solutions for resolving them.